Analisis Pengaruh Nilai Peak Ground Acceleration (PGA) Terhadap Story Shear Bangunan Bertingkat - Ahmad Hamidi - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2018)
This study aims to analyze and examine the effect of peak land acceleration value (PGA) on shear story using dynamic method of response spectrum. The PGA value and the spectrum response used are the spectrum responses issued by the PU ministry. The review is soft land in the citys in Riau. The results showed that the higher the story shear value, the higher the PGA value in each region. The areas with the highest inner and PGA grades are Pasir Pangarian (Rohul) and the lowest is Kota Selat Panjang (Meranti District). This is because the area of Rohul Regency is an area close to West Sumatera Province that has a high enough earthquake intensity when compared with Meranti Regency which is a coastal area located on the lower plains.